Zgromadzenia na terenie uczelni. Uwagi na tle Ustawy z dnia 20 lipca 2018 r. – Prawo o szkolnictwie wyższym i nauce - Pyrzyńska, Agata (Studia Prawa Publicznego, 2026)
The issue of freedom of assembly is among the most significant aspects of how any democratic state ruled by law functions. One specific type of assembly that exercise the freedom stipulated in Article 57 of the Constitution of the Republic of Poland is assemblies organized on university premises. These constitute an important tool for communicating positions and opinions, primarily by members of the academic community. However, due to the distinctive conditions under which higher education institutions operate, including the principle of university autonomy, the legislator decided to adopt special solutions regarding the organization of assemblies on university premises in the Law on Higher Education and Science, which constitutes a lex specialis to the Law on Assemblies. The aim of this article is to analyse the rules for organizing assemblies on university premises, including determining the extent to which the legislator has provided for specific exceptions in the organization of such assemblies compared to the rules set out in the Law on Assemblies. In particular, the discussion will take into account the constitutional principle of university autonomy, including the position of the rector and their specific duties regarding the maintenance of order and safety on university grounds. The analysis presents the statutory framework for organizing assemblies at higher education institutions, as well as the permissible discretion of university authorities in establishing internal regulations to further clarify this procedure. For the purposes of this study, the formal-legal method was used to examine the content, scope, and relationships between the applicable norms, alongside an analysis of the relevant literature and case law.